Targeted deletion in astrocyte intermediate filament (Gfap) alters neuronal physiology. - McCall, M A (1996)
Glial fibrillary acidic protein (GFAP) is a member of the family of intermediate filament structural proteins and is found predominantly in astrocytes of the central nervous system (CNS). To assess the function of GFAP, we created GFAP-null mice using gene targeting in embryonic stem cells. The GFAP-null mice have normal development and fertility, and show no gross alterations in behavior or CNS morphology. Astrocytes are present in the CNS of the mutant mice, but contain a severely reduced number of intermediate filaments. Since astrocyte processes contact synapses and may modulate synaptic function, we examined whether the GFAP-null mice were altered in long-term potentiation in the CA1 region of the hippocampus. The GFAP-null mice displayed enhanced long-term potentiation of both population spike amplitude and excitatory post-synaptic potential slope compared to control mice. These data suggest that GFAP is important for astrocyte-neuronal interactions, and that astrocyte processes play a vital role in modulating synaptic efficacy in the CNS. These mice therefore represent a direct demonstration that a primary defect in astrocytes influences neuronal physiology.